PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) MELALUI PROGRAM BINAAN DI PROVINSI BALI - Ni Nyoman Sunariani; A A N Oka Suryadinatha Gorda; Ida IDM Rai Mahaputra (Universitas Pendidikan Nasional, 2017)
ABSTRACTUMKM in national economy play an important role and strategic for the economic growth, not only in developing countries like Indonesia but also in developed countries. Nine district of a city that has the potential strategic support revenue in the area.Local revenue Bali Province to decrease from year 2015 it is only of 41,29 %, is much lower compared to last 2014 of 60,92 %. Which is due by UMKM sector.This condition is making UMKM very reasonable and potentially more empowered.In 2010, especially UMKM sector experienced a decline in the value exsport from year to year, declined significantly. From research exploratif to the field , problems identification , with AHP ( analitical hierarchy process ) found way UMKM, in Bali Province , who improve significantly sales good for the domestic market and exports Bali Province .This empowerment , in acceleration regional economic growth , job creation and the increase in competitiveness UMKM products .The research results show factors barrier UMKM, namely capital , human resources , access banking , of the nature of products lifetime short , and the limited market access good in the market national and international .Program under the jurisdiction of UMKM in Bali Province be done in collaborate with the government , banking , soe , cooperatives , lpd , bumd , college collaborated through an incubator business .Based on the research done , can formulated policy recommendations , under the jurisdiction of program partner between the government and UMKM in Bali Province. The government needs to simplification licensing procedure, cheap and fast through one roof.